Sulfur Source, Rate, and Methods of Application for Polyethylene-mulched Tomato - Anas D. Susila; Salvadore J. Locascio (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2005)
Tomato (Lycopersicon esculentum L.) was grown with polyethylene mulch and drip irrigation on a Millhopper fine sandy soil testing very high in P and low in organic matter during two seasons to evaluate the effect of S source, rate, and application methods on plant growth and yield of fruit.  Sulfur rate of 34 and 68 kg S.ha-1 were applied with  preplant (broadcast in the bed), drip (10 weekly drip application), and  by split applications (50% preplant and 50% drip).  In split applications, S sources evaluated were ammonium sulfate and ammonium thiosulfate.  Plant height was increased with S application from 0 to 68 kg S.ha-1 in both studies. However, response on plant dry weight only occurred in spring 1999. Total marketable yield was 17.9 tons.ha-1 with 0 kg S.ha-1 and was increased linearly to 48.1 tons.ha-1 with application of 68 kg S.ha-1 in Spring 1999, but no response to S was obtained in the Spring 1998 study. Measured variables were not affected by S source and methods of application.  Increasing S application from 0  to 68 kg S.ha-1 reduced leaf and plant tissue P concentration 14 and 12% at mid season, 26 and 25% at  late season sampling times, respectively.  S application of 68 kg S.ha-1 reduced soil pH approximately 0.3 unit at the end of the season in both studies.   Key  words:  drip irrigation, sulfur,  fertigation, Lycopersicon esculentum